Development and evaluation of a tetravalent botulinum vaccine - Dan-Yang Shi; Fu-Jia Liu; Zhi-Ying Li; Yun-Yun Mao; Jian-Sheng Lu; Rong Wang; Xiao-Bin Pang; Yun-Zhou Yu; Zhi-Xin Yang (Taylor & Francis Group, 2022)
Botulinum neurotoxins (BoNTs) are the most toxic known proteins. Naturally occurring botulism in humans is caused by botulinum serotypes A, B, E, and F. Vaccination is an effective strategy to prevent botulism. In this study, a tetravalent botulinum vaccine (TBV) that can prevent serotypes A, B, E, and F was developed using the C-terminal receptor-binding domain of BoNT (Hc) as an antigen. To develop a suitable vaccine formulation, in vitro binding experiments of antigens and aluminum adjuvant in different buffers, and in vivo experiments of TBV at different antigen concentrations, were conducted. Our results showed that the optimal vaccine formulation buffer was a pH 6.0 phosphate buffer, and the suitable antigen concentration was 40 or 80 µg/ml of each antigen. A pilot-scale TBV was then prepared and evaluated for immunogenicity and stability. The results showed that TBV could elicit strong protective efficacy against each BoNT in mice, and remain effective after two years of storage at 4ºC, indicating that the preparation was stable and highly effective. Adsorption experiments also showed that the antigens could be well adsorbed by the aluminum adjuvant after 2 years of storage. Our results provide valuable experimental data supporting the development of a tetravalent botulinum vaccine, which is a promising candidate for the prevention of botulinum serotypes A, B, E, and F.